Business plans kit for dummies - Peterson, Steven (Wiley, 2010)
Discover the ins and outs of constructing a great business plan. When you?re establishing, expanding, or re-energizing a business, the best place to start is writing your business plan. Not only does writing out your idea force you to think more clearly about what you want to do, it will also give the people you work with a defined road map as well. Business Plans Kit For Dummies, 3rd Edition has been updated to give you the very latest information on the changing economy and its impact on business plans; dealing with venture capitalists; getting start-up money in any economy; incorporating so.
Print version record
Keywords: Business planning; Strategic planning; Planification stratégique; BUSINESS & ECONOMICS; Strategic Planning; Bedrijfskunde; Ondernemingsgeest